-3+3(x-1)+4x=

Simple and best practice solution for -3+3(x-1)+4x= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3+3(x-1)+4x= equation:



-3+3(x-1)+4x=
We move all terms to the left:
-3+3(x-1)+4x-()=0
We add all the numbers together, and all the variables
4x+3(x-1)=0
We multiply parentheses
4x+3x-3=0
We add all the numbers together, and all the variables
7x-3=0
We move all terms containing x to the left, all other terms to the right
7x=3
x=3/7
x=3/7

See similar equations:

| 5x−12x+24=−11 | | 23=5/9v-2 | | -4(-2+4n)=n-26 | | 4+(-6+2x)= | | 3x-2=0+6 | | 4h-10=30 | | 10(2x+3)= | | -8-3(2+6n)=34-2n | | (8+9x)6= | | 4(5x-³)=500 | | -3(-7+2k)=18-3k | | x+4/−2=8 | | P+12=2p+6 | | √x+2-5=3 | | -5(6x-7)+x=35+2x | | 9^4x-11=9^13 | | -36+4x=-6(-x+7) | | 0.03*x=0.5 | | y+3/4y= | | 6a−3a=1 | | 41=1/2(132-x) | | 5y=9=8y | | 5(-3x+2)-x=-8x+34 | | -3q=7=4q | | 30x-6=-66 | | 4n+8n=72 | | -4y=0+-12 | | 3x+2(x+5)=62 | | 3y=-12y | | 3x+2(x+5)=60 | | 22=x+4 | | 2y=0+-4 |

Equations solver categories